Relationship between orofacial pain and absenteeism among workers in Southern Brazil - Anderson Nardi; Edgard Michel Crosato; Maria Gabriela Haye Biazevic; Edgard Crosato; Eduardo Pizzatto; Dagmar de Paula Queluz (Universidade Estadual de Campinas, 2015)
Aim: To verify the relationship between orofacial pain and absenteeism in workers of slaughter and meat processing industries in the Southern region of Brazil. Methods: A cross-sectional study, with the random sample of 401 workers of slaughter and meat processing industries in the Southern region of Brazil, was carried out. A questionnaire referred to the situation of absenteeism caused by nine different types of orofacial pain and also the amount of time the employee was kept from work. Results: Only 60 workers (15%) reported having missed work due to orofacial pain in the six months prior to the study. The prevalence of absenteeism resulting from orofacial pain was of 15%. The types of orofacial pain that resulted in absenteeism were: spontaneous toothache (9.7 %); toothache caused by cold or hot liquids or by sweet foodstuff (6.5%) and pain around and behind the eyes (3.2%). There was a predominance of absenteeism in half and full work shifts for the types of orofacial pain experienced. Associations between absenteeism from induced toothache and gender (p < 0.05), absenteeism and spontaneous toothache and family income (p = 0.011), and between absenteeism and the self awareness of their oral health condition, as well as the nine types of orofacial pain (p < 0.001) were observed. Conclusions: The prevalence of absenteeism as a result of orofacial pain was low.